The possibility of application of xanthan in removal of metal ions from wastewaters - Ida Zahović; Zorana Rončević; Jelena Dodić; Jovana Grahovac; Siniša Dodić (Journal of Engineering & Processing Management, 2017)
Biopolymers have the ability to absorb large amounts of water or biological fluids. They are swelling and forming hydrogels. Thanks to this, they have found a variety of applications, and among others they can be used to remove some metal ions from the water. Due to its unique structure and exceptional rheological characteristics, microbiological biopolymer, xanthan, can also be used for purification of wastewater because structures formed in the presence of metals can be easily separated.Therefore, the research from this paper was carried out in order to examine the possibilities of crosslinking the xanthan with different metal ions. Based on the successful crosslinking and stability of the formed crosslinked structures, it has been estimated that with the use of this biopolymer it is possible to remove ions of lead and iron from wastewaters.
Keywords: removal of metal ions; wastewaters; xanthan